1996
DOI: 10.2307/2061761
|View full text |Cite
|
Sign up to set email alerts
|

Education and the changing age pattern of American fertility: 1963–1989

Abstract: Using pooled data from the 1980, 1985, and 1990 Current Population Surveys, we describe fertility trends by age and education for the period 1963-1989. Interest focuses on whether the effects of education have changed across this period. We show that women with college degrees experienced dramatic shifts toward later ages of childbearing. This shift is consistent with arguments we develop about the increased opportunity for women to pursue careers and about changes in the availability of child care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
164
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(187 citation statements)
references
References 26 publications
13
164
1
9
Order By: Relevance
“…While the influence of shifting educational and occupational distributions of the female population on childbearing decisions has been visited (Rindfuss et al 1996) and revisited (Kögel 2004;Engelhardt and Prskawetz 2004;Adserà 2004), the relevant effect of changing male distributions remains under-studied. A decomposition method is therefore applied to dissociate the impact of compositional effects (education differentials and employment status variations) from behavioral effects (fluctuations in fertility) on the above-mentioned variations of TFR.…”
Section: Methodsmentioning
confidence: 99%
“…While the influence of shifting educational and occupational distributions of the female population on childbearing decisions has been visited (Rindfuss et al 1996) and revisited (Kögel 2004;Engelhardt and Prskawetz 2004;Adserà 2004), the relevant effect of changing male distributions remains under-studied. A decomposition method is therefore applied to dissociate the impact of compositional effects (education differentials and employment status variations) from behavioral effects (fluctuations in fertility) on the above-mentioned variations of TFR.…”
Section: Methodsmentioning
confidence: 99%
“…Research shows that the delay in childbearing is more marked when having children later in life is culturally approved (Morgan 1991). It has also been argued that flexible and loose age norms are some of the reasons for the changes in the timing of childbearing (Castro Martin 1992; Rindfuss et al 1996;Settersten and Haegestad 1996). Therefore, it seems justified to suspect that the sustained patterns of early childbearing are supported by more universal and strict age norms.…”
Section: Polish Case: Timing Of Transition To Parenthoodmentioning
confidence: 99%
“…Whereas several studies have shown that women's educational attainment has a negative effect on various childbearing outcomes (e.g., Bloom and Trussell 1984;Happel et al 1984;Marini 1984;Blossfeld and Huinink 1991;Blackburn et al 1993;Rindfuss et al 1996;Gustafsson and Wetzels 2000;Yang and Morgan 2004), others have found positive relationships between educational attainment and fertility after first birth (e.g., Joshi 2002;Kreyenfeld 2002;Köppen 2006;Gerster et al 2007;Kravdal 2001Kravdal , 2007. This challenges the idea that opportunity costs outweigh a positive income effect among highly educated women.…”
Section: Theoretical Considerations and Previous Research 21 Educatimentioning
confidence: 99%